Os efeitos do comportamento sedentário nas funções cognitivas, capacidade funcional e qualidade de vida em idosos: revisão narrativa - Cunha, Ariany Cristyny Mourão da (Brasil, 2021)
Sedentary lifestyle can be understood as the reduction or absence of physical activities, being associated with new habits provided by modern society. Recent data has shown that sedentary habits seem to compromise some health indicators in the elderly. Therefore, this work intends to verify the disposition of the literature on the effects of sedentary behavior on cognitive functions, functional capacity and quality of life in the elderly. In order to achieve the objectives proposed in this study, the methodological approach was based on qualitative research, using bibliographic research as a procedure method, resulting in a narrative review. The construction of this review included authors and their respective works that address the respective theme. The literature suggests that sedentary behavior interferes with the regular practice of activities of daily living (ADL's), favoring the emergence of chronic-degenerative diseases. Consequently, sedentary behavior seems to be contributing to the decline of cognitive functions, highlighting the parameters of memory and information storage. Regarding quality of life, the literature suggests that sedentary behavior promotes the occurrence of a deficit of autonomy and independence, resulting in low self-esteem, social and family isolation. Thus, we consider that the reduction of sedentary behavior through physical activity in the elderly population is considered a fundamental resource in the maintenance of functional capacities, as well as strengthening emotional and social aspects and improving quality of life.